Talent development, existential philosophy and sport. On becoming an elite athlete - Aggerholm, K. (Ethics and sport, 2015)
'Why don`t young athletes in sport just quit?` Starting with this question and drawing on existential philosophy, phenomenology and hermeneutics, Talent Development, Existential Philosophy and Sport seeks a deeper understanding of the experience of being a talented young sportsperson striving to become an elite athlete.